Strategi Guru PAI Dalam Menanamkan Moderasi Beragama Di SMA Islam Multikultural - ridhwan; Muh. Hanif (JURNAL DIKDAS, 2026)
This study analyzes how Islamic Education (PAI) teachers instill religious moderation (wasathiyah) within the multicultural environment of SMA Boarding School Putra Harapan, examined through the lens of agency and structure theory. The research aims to explore the interplay between teachers’ strategic capacity and institutional support in a diverse student body characterized by varying regional origins, socioeconomic statuses, and religious organizations. Using a qualitative case study approach, data were gathered through in-depth interviews, participant observations, and document analysis. The main results demonstrate that PAI teachers, acting as key agents, successfuly integrate tolerance, humanity, and national commitment into the curriculum. This is achieved through collaborative digital-mediated teaching and practical daily habits, such as visiting non-Muslim neighbors and conducting friendship visits to Christian schools. Structurally, the Abdul Mukti Islamic Foundation enables this process by aligning its vision, funding facilities, providing professional workshops, and conducting academic supervision. Structural constraints are limited to potential intra-religious friction regarding school thought variations and managing inclusive students. In conclusion, instilling religious moderation in a multicultural boarding school operates effectively due to a strong dialectic between the strategic agency of teachers and the adaptive, supportive institutional structure.